Paul and pseudepigraphy - Porter, Stanley E. 1956- (Leiden [u.a.] Brill, 2013)
On Pauline pseudepigraphy: an introduction / Stanley E. Porter and Gregory P. Fewster -- 1. Critical issues in Pauline pseudepigraphy. Authorship and pseudepigraphy in early Christian literature: a translation of the most important source texts and an annotated bibliography / Armin D. Baum -- Pauline chronology and the question of pseudonymity of the Pastoral Epistles / Stanley E. Porter -- Hermeneutical issues in canonical pseudepigrapha: the head/body motif in the Pauline corpus as a test case / Gregory P. Fewster -- Style and pseudonymity in Pauline scholarship: a register based configuration / Andrew W. Pitts -- The problem of the Pastoral Epistles: an important hypothesis reconsidered / Jermo van Nes -- 2. Pauline pseudepigraphy within the Christian canon. A deutero-Pauline mystery?: ecclesiology in Colossians and Ephesians / Sigurd Grindheim -- The imitation hypothesis: pseudepigraphic remarks on 2 Thessalonians with help from documentary papyri / Christina M. Kreinecker -- Christology, Greco-Roman religious piety, and the pseudonymity of the pastoral letters / Linda L. Belleville -- Hebrews as an instructional appendix to Romans / Clare K. Rothschild -- The epistolory closing of Hebrews and Pauline imitation / Bryan R. Dyer -- 3. Pauline pseudepigraphy outside the Christian canon. Dusting off a pseudo-historical letter: re-thinking the epistolary aspects of the apocryphal Epistle to the Laodiceans / Philip L. Tite -- The pseudepigraphical correspondence between Seneca and Paul: a reassessment / Ilaria L.E. Ramelli -- The heretics' apostle and two Pauline pseudepigrapha from Nag Hammadi / Michael Kaler
In this book, an international group of scholars engage open questions in the study of the Apostle Paul and those documents often deemed pseudepigraphal. This volume addresses many traditional questions, including those of method and the authenticity of several canonical Pauline letters, but it also reflects a desire to think in new ways about persistent questions surrounding pseudepigraphy. The focus on pseudepigraphy in relationship to Paul affords a unique opportunity to address this innovative inclination, not readily available in studies of New Testament pseudepigraphy in general. Regarding these concerns, new approaches are introduced, traditional evidence is reassessed, and some new suggestions are offered. In addition to Pauline letters, treatments of related non-canonical Pauline pseudepigraphs are included in discussion
Includes bibliographical references and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Paulus -- Apostel, Heiliger; Bible -- Authorship; Bible -- Extra-canonical parallels; Bible -- Criticism, interpretation, etc; Bible -- Authorship; Bible -- Extra-canonical parallels; Bible -- Criticism, interpretation, etc; Bibel; Bibel; Aufsatzsammlung; Pseudepigraphie; Apokalyptik; Aufsatzsammlung